2023
DOI: 10.3390/cancers15030580
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Node-RADS Scoring System for a Standardized Assessment of Regional Lymph Nodes in Bladder Cancer Patients

Abstract: Background: Current cross-sectional imaging modalities exhibit heterogenous diagnostic performances for the detection of a lymph node invasion (LNI) in bladder cancer (BCa) patients. Recently, the Node-RADS score was introduced to provide a standardized comprehensive evaluation of LNI, based on a five-item Likert scale accounting for both size and configuration criteria. In the current study, we hypothesized that the Node-RADS score accurately predicts the LNI and tested its diagnostic performance. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…However, Node-RADS achieved a high AUC of 0.94 in diagnosing lung cancer lymph node metastasis 11 and a high AUC of 0.91 in bladder cancer. 12 Our research showed more outstanding diagnostic performance in NPC, providing new possibilities for the extensive application of Node-RADS.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, Node-RADS achieved a high AUC of 0.94 in diagnosing lung cancer lymph node metastasis 11 and a high AUC of 0.91 in bladder cancer. 12 Our research showed more outstanding diagnostic performance in NPC, providing new possibilities for the extensive application of Node-RADS.…”
Section: Discussionmentioning
confidence: 59%
“…Node-RADS has shown encouraging diagnostic performance in prostate, lung, and bladder cancer since it launched in 2021. 10 - 12 However, no previous report has explored its role in NPC. We assumed that higher Node-RADS scores are correlated with a higher risk of CLN metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found an increased specificity (1.00 vs. 0.08–0.19), while sensitivity decreased (0.17 vs. 0.96–1.00) and AUROC remained unchanged (0.58 vs. 0.57–0.60, respectively) compared to validated nomograms [ 23 ]. Leonardo et al investigated the performance of Node-RADS in bladder cancer and demonstrated a moderate-to-high overall accuracy for malignant lymph node invasion with an AUROC of up to 0.91, and the option of setting different cut-off values according to specific clinical scenarios [ 24 ]. Meyer et al assessed lung cancer patients using Node-RADS and radiomics [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the presence of muscle invasion represents an unfavorable prognostic indicator. Despite advances in imaging diagnostics [4,5], a portion of patients already harbors micrometastases at the time of diagnosis [6,7].…”
Section: Introductionmentioning
confidence: 99%